Can responsive deep brain stimulation be a cost‐effective treatment for severe obesity?. Issue 2 (27th January 2022) - Mahajan, Uma V.; Ojukwu, Disep I.; Azagury, Dan E.; Safer, Debra L.; Cunningham, Tricia; Halpern, Casey H.
Abstract: Objective: A first‐in‐human responsive deep brain stimulation (rDBS) trial (NCT03868670) for obesity is under way, which is based on promising preclinical evidence. Given the upfront costs of rDBS, it is prudent to examine the success threshold for cost‐effectiveness compared with laparoscopic Roux‐en‐Y gastric bypass (LRYGB). Methods: Efficacy and safety data on LRYGB and safety data on rDBS were collected for established indications through a literature search. The success threshold was defined as minimum BMI reduction. Treatment costs were calculated via Medicare national reimbursement data. Results: LRYGB had a mean BMI reduction of 13.75 kg/m 2 . Based on adverse events, LRYGB was a less‐preferred health state (overall adverse event utility of 0.96 [0.02]) than rDBS (0.98 [0.01]), but LRYGB ($14, 366 [$6, 410]) had a significantly lower treatment cost than rDBS ($29, 951 [$4, 490]; p < 0.0001). Therefore, for rDBS to be cost‐effective compared with LRYGB, the multiple models yielded a success threshold range of 13.7 to 15.2 kg/m 2 . Conclusions: This study established a preliminary efficacy success threshold for rDBS to be cost‐effective for severe obesity, and results from randomized controlled trials are needed. This analysis allows for interpretation of the economic impact of advancing rDBS for obesity in light of ongoing trial results and suggests an attainable threshold is needed for cost‐effectiveness.